Investigating the Effect of Customer Experience, Perceived Value, and Customer Satisfaction on Environment-Friendly Behavior - Üzeyir Kement; Evren Güçer; Sinan Çavuşoğlu; Bülent Demirağ (Universitas Pasundan, 2021)
In line with the model proposed within the scope of the research, this study seeks to achieve the following goals: 1) to examine the effect of experience on perceived value, 2) to determine the effect of the sub-dimensions of perceived value on customer satisfaction, and 3) to determine the effect of customer satisfaction on environment friendly behavior. The study was conducted on individuals who participated in the camping activities in the Black Sea region of Turkey. The results show that feel, relate, and act experiences have positive effects on functional value, while sense, feel, and act experiences have positive effects on social value. Additionally, sense, feel, relate, and act experiences show positive effects on emotional value, while sense, feel, and act experiences have positive effects on epistemic and conditional values. On the other hand, the think experience, located in the experience dimensions, does not affect any sub-dimension of perceived value. In conclusion, the sub-dimensions of the perceived value affect customer satisfaction, and customer satisfaction positively affects environmentally friendly behavior.